ShareTrust: Centralized trust management mechanism for trustworthy resource sharing in industrial Internet of Things. (May 2022) - Din, Ikram Ud; Awan, Kamran Ahmad; Almogren, Ahmad; Kim, Byung-Seo
Abstract: Internet of Things (IoT) provides a platform where nodes are connected through a wireless medium for sharing information. In IoT, some nodes cannot perform complex operations and computation, and require adequate processing power to perform such operations. To address such challenges, the concept of resource sharing becomes a notable solution by which nodes can share their unoccupied resources. This paper proposes a trust management mechanism to distinguish malicious and compromised nodes for maintaining trustworthiness in a resource sharing interface. The proposed mechanism integrates the trust module for the allocation of resources to nodes for a short period of time. Trust computation also involves trust aggregation wherein the previous trust degree is aggregated with the current one for formulating an absolute trust degree. The proposed approach, named ShareTrust, has been evaluated by performing extensive simulations where the results show better performance of the proposed scheme to maintain trustworthiness in the IoT environment. Graphical abstract: Highlights: Resource sharing is a solution for IoT to avoid complex processing and computation. ShareTrust classifies malicious and compromised nodes for maintaining trustworthiness. ShareTrust integrates the trust module for resource allocation for a short time.